Measurement of Oral Health Literacy Level Among Bangladeshi Adults Seeking Dental Care and Its Relationship With Socio-demographic Characteristics - Mahmud, Shaikh Zakir; Amin, Mohammad Shoheilul; Tarafder, Monowar Ahmad; Hossain, Sarder Mahmud (Anwer Khan Modern Medical College Journal, 2017)
Background: The important role of socio-economical factors in oral health and disease has been identified. Oral health literacy is associated with inaccurate knowledge about preventive measures such as proper brushing, dental care visits and oral health-related quality of life. Like general health literacy, oral health literacy incorporates the capacity a person has to learn and use information about oral health in making decisions about their oral health. Objective: This analytic type of cross sectional study was conducted to measure the Oral Health literacy Level (OHLL) and its relationship with socio-demographic characteristics among Bangladeshi adults seeking dental care. Materials and Methods: A total 100 subjects attended at the out patient's Dental Department of Ibrahim General Hospital-Mirpur for routine dental checkup over a period of six months from August 2014 to January 2015 fulfilled the eligibility criteria were selected consecutively. Pre-tested semi structured interviewer administrated questionnaires were used to collect the information. Cross tabulations and associations were determined by using the Chi-square test where applicable. Results: The mean oral health literacy score was 15.51 out of 30 and SD ±4.806 with 7% of respondents had very poor OHLL, 49% had poor OHLL, 41% had fair and 3% had excellent oral health literacy level. Oral health literacy level found more in age group of 30-39 years. The majority of excellent oral health literacy level was from graduate and above group. In addition, patients' sex, marital status and occupation were significantly associated with oral health literacy level as the P-values were 0.008, 0.002 and 0.021 respectively. Conclusion: Patients with inadequate oral health literacy were consistently more likely to report poor oral health than patients with adequate literacy skills. Future studies are needed to determine whether this framework is supported by empirical data and leads to improvements in oral health and reductions in health disparities. Anwer Khan Modern Medical College Journal Vol. 7, No. 1: Jan 2016, P 34-39